Tourist needs for urban open public spaces in Kish Island, Iran - Salim, Mona Erfanian (2012)
Small Islands are supposed to meet tourists’ needs in sustainable tourism development. This study posits that landscape design can improve sustainable tourism development through the quality of urban open public spaces (UOPS) while supporting tourists’ needs at the same time. Kish Island in south of Iran matches the Small Island characteristics and is identified as an important tourism zone based on national strategies. Nevertheless, in the development guidelines of Kish, the principle of sustainable tourism is lacking and the urban open public space does not address appropriately the tourists’ needs. Thus, this research was carried out to understand the tourists’ needs for UOPS of Kish with the aim to improve the urban design in a sustainable approach. This is realized by identifying the concepts related to tourists’ needs, exploring the factors affecting their needs, and interpreting the relationship between them. This research employed case study as the main strategy of the research. The study was designed in four stages. The first stage reviewed the background of the tourists’ needs and the design of UOPS in the overall domain and Kish Island to identify the issues and develop the research questions. It also developed a conceptual framework and research methodology in the second stage. Consequently in the third stage, the research was conducted in Kish as case study. The study adopted a mixedmethodological approach in data collection and analysis. Data was collected from the field observation of two selected sites, semi-structure interview with experts, and a survey of Kish tourists. The final results were derived from a convergence of the data in an analytical triangulation process. The findings of this study provide insights into designing UOPS, while taking into account the tourists’ needs and sustainable development in a Small Island. The results mostly confirmed all the proposed themes for the tourists’ needs in Kish and the effective factors, although reject significance of some variables. The study developed an analytical format that could predict how urban design could meet the tourists’ needs in UOPS of Kish and improve its development toward sustainable tourism. The research actually established new practical approaches to meet the tourists’ needs as an urgent assist for contemporary thinking. It could be employed as a base for future research and projects at Kish and other similar Tourism Islands. Additionally, each approach used in enhancing tourism development in Kish will definitely assist in developing the tourism industry in the country. The results finally could be generalized to other tourist destinations in Iran or other countries with similar climate and culture.